Prediction of intracranial hemorrhages after mechanical thrombectomy of basilar artery occlusion - Neuberger, Ulf; Seker, Fatih; Schönenberger, Silvia; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Pfaff, Johannes; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2019)
Background: Mechanical thrombectomy (MT) achieves high recanalization rates in basilar artery occlusion (BAO). A severe complication of MT in BAO is intracranial hemorrhage (ICH). Yet, knowledge of risk factors for ICH after MT in BAO is limited. Objective To evaluate clinical and procedural parameters of patients treated with MT owing to BAO to identify potential risk factors for ICH—in particular, symptomatic ICH (sICH), and assess their clinical relevance. Methods: We conducted a retrospective analysis of 101 consecutive patients presenting with BAO, who were treated with MT in our centre. Important clinical and procedural parameters were analysed as possible predictors for any ICH and sICH according to the Heidelberg Bleeding Classification using univariate tests and multivariate logistic regressions. Results ICH occurred in 25 (24.8%) patients, with a total of 7 (6.9%) developing sICH. Treatment with glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitors was independently associated with any ICH (OR=24.67, 95% CI 4.90 to 124.03) and sICH (OR=7.08, 95% CI 1.36 to 36.78). Also, a longer onset-to-recanalization time increased the risk of both any ICH (OR=1.17, 95% CI 1.07 to 1.31) and sICH (OR=1.22, 95% CI 1.08 to 1.42). Higher serum glucose levels were associated with a higher incidence of any ICH (OR=1.39, 95% CI 1.06 to 1.85) and a higher risk of a fatal outcome (OR=1.03, 95% CI 1.01 to 1.05). Conclusion: Administration of GPIIb/IIIa inhibitor during the course of MT of BAO was identified as an important risk factor in the development of any ICH and sICH.